2016
DOI: 10.1259/bjr.20150850
|View full text |Cite
|
Sign up to set email alerts
|

Individually tailored contrast enhancement in CT pulmonary angiography

Abstract: Objective: The purpose was to evaluate individually shaped contrast media (CM) delivery in CT pulmonary angiography (CTPA) for suspected pulmonary embolism (PE). Methods: 100 consecutive emergency patients with clinical suspicion of PE were evaluated. High-pitch CTPA was performed on a second-generation dual-source CT using the following parameters: 100 kV, 200-250 mAsref, rotation time 0.28 s, 128 3 0.6 mm col. and image reconstruction 1.0/0.8 mm (B30f). Group 1 (n 5 50) then received a fixed CM bolus (300 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 45 publications
0
29
0
5
Order By: Relevance
“…Current literature advocates for flow rates in CTPA not below 1.2 g iodine / second [30]. Though our reconstruction algorithm results in an almost twofold CNR increase, we reduced the flow rate to 0.6 g iodine / second in the low CM dose group.…”
Section: Methodsmentioning
confidence: 95%
“…Current literature advocates for flow rates in CTPA not below 1.2 g iodine / second [30]. Though our reconstruction algorithm results in an almost twofold CNR increase, we reduced the flow rate to 0.6 g iodine / second in the low CM dose group.…”
Section: Methodsmentioning
confidence: 95%
“…A recent study has shown that pulmonary CTA should be performed in the resting expiratory position [25]. The image quality of pulmonary artery depiction in CTA can be further improved by using a weight-adapted contrast bolus [26]. Another possible solution would be to increase the injection duration, however at the cost of more contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hendriks et al (41) used protocols adjusted for patient weight and scan duration, employing automated software that calculates CM amount and flow rate and showed a substantial CM volume reduction in low-weight subjects compared with standard "fixed" protocols. Therefore, a solution could possibly be found in individualizing contrast application for each patient.…”
Section: Pulmonary Ctamentioning
confidence: 99%